2006
DOI: 10.1093/rheumatology/kel040
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, reliability and validity of the German Shoulder Pain and Disability Index (SPADI)

Abstract: The German SPADI is a practicable, reliable and valid instrument, and can be recommended for the self-assessment of shoulder pain and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
100
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 17 publications
14
100
0
8
Order By: Relevance
“…Only 1 previous study assessed agreement for the Quick-DASH, 34 and 2 for the SPADI, 1,15 and the results were consistent with those of the present study.…”
Section: Internal Responsivenesssupporting
confidence: 91%
“…Only 1 previous study assessed agreement for the Quick-DASH, 34 and 2 for the SPADI, 1,15 and the results were consistent with those of the present study.…”
Section: Internal Responsivenesssupporting
confidence: 91%
“…Studies of the SPADI have indicated adequate measurement properties. 15,115 The MDC at the 90% confidence level has been reported to be 18.1, 118 the MDC at the 95% confidence level has been reported to be 18.0, 3 and the minimal clinically important difference has been reported to be 8.0 98 Clinicians should use validated functional outcome measures, such as the DASH, the ASES, or the SPADI. These should be utilized before and after interventions intended to alleviate the impairments of body function and structure, activity limitations, and participation restrictions associated with adhesive capsulitis.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Initially, the SPADI was proposed in Visual Analogue Scale (VAS) 6 , and subsequently validated on Numeric Rating Scale (NRS) 22 and cross-culturally adapted and validated for German 23 and Slovak 24 languages. Several studies have supported the use of SPADI on clinical practice and research [25][26][27][28] , since it is a specific questionnaire for the shoulder joint; has all the psychometric properties evaluated; has short questions with answers in NRS format that facilitate its completion, requiring about 3 to 10 minutes to be completed 22,25,26 .…”
Section: Introductionmentioning
confidence: 99%